Myofascial pain syndrome. Literature update on the subject of a clinical case - Landa Román, Cristóbal (2017)
This article summarizes a literature evaluation of the past 17 years in relation to the myofascial pain syndrome in which the most relevant information for a diagnosis is collected, also presents a clinical case in which psychological etiology that began the pathological disorder could be determined. The case of a patient with decrease in the mouth opening, myalgia and points trigger muscle masseter and temporal is presented. Pain myofascial was diagnosed after muscle testing, radiographic and laboratory exams in order to exclude systemic etiologies. The indicated treatment consisted in the application of a splint occlusal, physiotherapy, relaxing muscles, corticosteroids, anti-inflammatories and the consultation with psychologist. In the first appointment an oral opening of 1.2 cm was recorded, in the second appointment the record was 1.6 cm, in the last query the record was 4.8 cm after drug treatment in conjunction with professional in psychology. It is concluded that psychological problems has a major impact in gnatologic system and psychological consultation turned out great support for this syndrome.